THE CLASSICAL CEPHEIDS' HISTOGRAMS OF PERIODS DISTRIBUTION - Bezdenezhnyj, V. P. (Одеські астрономічні публікації, 2007)
On the base of GCVS sampling has been carried out the analysis of periods of classical Cepheids. We have studied the histograms of periods distributions for the stars with small amplitudes (DCEPS) and large ones (DCEP) separately . These two histograms have different sight (amplitudes of the peaks), but their peaks follow to general sequence. We have given the modal interpretation of the histograms on the base of mode identifications.